[BP.03.04] LONG-TERM IMPACT OF ELEVATED BLOOD PRESSURE IN CHILDHOOD ON ADULT SUBCLINICAL CARDIOVASCULAR DISEASES: EVIDENCE FROM CHINA. (September 2017) - Yan, Y.; Liu, J.; Hou, D.; Zhao, X.; Cheng, H.; Mi, J.
Abstract : Objective: Hypertension is the main risk factor for cardiovascular disease. The association between childhood elevated blood pressure and adult subclinical cardiovascular diseases has been reported in several longitudinal studies from Europe, US and Australia. We aimed to examine the long-term impact of elevated blood pressure (BP) from childhood on subclinical cardiovascular diseases and chronic kidney disease in a China population. Design and method: Data were obtained from a school-based prospective study, which consisted of 1256 adults aged 27–42 years who had 2–10 measurements of body mass index (BMI) and blood pressure from childhood in 1987. The total area under the growth curve (AUC) and incremental AUC from childhood to adulthood were calculated to characterize the cumulative risk burden and long-term trends of BMI and BP during the follow-up duration. In the final survey (2010), we measured multiple markers of subclinical cardiovascular diseases and chronic kidney disease, including carotid intima-media thickness (cIMT), carotid-femoral pulse wave velocity (cfPWV), left ventricular mass (LVM), and microalbumin (MAU) were measured. Results: Pearson correlation analyses showed that BP in childhood and adulthood, as well as cumulative and incremental values from childhood to adulthood, were all significantly associated with adult cIMT, cfPWV, LVM, and MAU in males and in females (all P < 0.05). In the multivariate logistical analyses, for both genders, childhood SBP predicted hypertension, high cIMT, high cfPWV, high LVM and high MAU in adulthood. However, the associations for high Cimt, high cfWV, high LVM and high MAU were largely attenuated and became non-significant after additional adjustment for adult BP and other risk factors, except that childhood BP showed a borderline significant association with high cfPWV in adulthood for males. In addition, for both genders, incremental BP from childhood to adulthood predicted high cIMT, high cfPWV, high LVM and high MAU in adulthood independent of childhood values. Conclusions: Both elevated BP from childhood and incremental BP from childhood to adulthood play important roles in the development of subclinical cardiovascular diseases and chronic kidney disease in adulthood.